Music and arts festivals as platforms for enhancing Sustainable Development - Lopez, Gomez Camila (Department of Environmental and Geographical Science, 2022)
Humanity is going through a complex process of historical transformation in which the consolidation of a new paradigm – Sustainable Development – is required in order to tackle current unprecedented global crises such as Climate Change and the COVID-19 pandemic. In congruence with this harsh reality, the 2030 Agenda on Sustainable Development can be regarded as an urgent call aimed at individuals, communities, institutions and nations, centred on the imperative need to create the structural foundations of a socially just and environmentally safe world. This research explores different ways in which contemporary music and arts festivals might operate as platforms for enhancing Sustainable Development. The central idea is to explore the way in which music and arts festivals, through strategies of socio-environmental awareness and education, community building and social participation, contribute to the consolidation of sustainable development as a new paradigm. This specific research is centred on the analysis of three organizations, Greenpop and Cape Town Carnival based in South Africa and Green Music Initiative based in Germany: organizations that actively participate in the arrangement and operation of different music and arts festivals. This selection was based on the belief that the analysis of cross-cultural cases enriches the understanding of the way in which festivals can effectively contribute to the process of encouraging the emergence and consolidation of a more sustainable world view. These three organizations are currently facing challenges and opportunities that arise from local and global processes of environmental damage and social exclusion. The key learnings of this research reflect the important role that festivals, through their promotion of creativity and community building, play in the generation of socio-environmental knowledge, in the generation of social cohesion and social capabilities, also in the experimentation and action of possible solutions to environmental global crises such as climate change and land use change. In its final section, this document also presents some of the key learnings that the festival industry has developed from the current COVID-19 pandemic and reflects upon the way in which these learnings can strengthen its role in the consolidation of the sustainable development paradigm.